Weathered words : formulaic language and verbal art - Frog; Lamb, William (Publications of the Milman Parry Collection of Oral Literature, 2022)
"Formulaic phraseology presents the epitome of words worn and weathered by trial and the tests of time. Scholarship on weathered words is exceptionally diverse and interdisciplinary. This volume focuses on verbal art, which makes Oral-Formulaic Theory (OFT) a major point of reference. Yet weathered words are but a part of OFT, and OFT is only a part of scholarship on weathered words. Each of the eighteen essays gathered here brings particular aspects of formulaic language into focus. No volume on such a diverse topic can be all-encompassing, but the essays highlight aspects of the phenomenon that may be eclipsed elsewhere: they diverge not only in style, but sometimes even in how they choose to define "formula." As such, they offer overlapping frames that complement one another both in their convergences and their contrasts. While they view formulaicity from multifarious angles, they unite in a Picasso of perspectives on which the reader can reflect and draw insight"--
Keywords: Oral-formulaic analysis; formulat (kerronta); formula-analyysi; suullinen perinne; kansanrunous; kieli ja kielet; kansanrunot; kertomusperinne; kertomarunot; kalevalamittaiset runot; itkuvirret; folkloristiikka; kirjallisuudentutkimus; narrativa formler; formelanalys; muntlig tradition; folkdiktning; språk; folkdikter; berättartradition; episka dikter; dikter på kalevalamått; gråtkväden; folkloristik; litteraturvetenskap; multiformit